Exploring Regulation of Chinese Medicine on Osteoclasts Based on OPG/RANKL/RANK Signaling Pathway - Chutian ZHANG; Yanping LIN (康复学报)
As the balance of bone metabolism, osteoclasts are closely related to the quantity and activity of bone metabolism. The discovery of osteoprotegerin (OPG) /RANKL/RANK signaling pathway is a new breakthrough in the study of bone metabolism as the key of maintaining bone balance. Important molecular regulatory mechanisms play a key role in osteoclast precursor cell differentiation and bone resorption, and are the new directions in anti-osteoporosis drug research. Traditional Chinese medicine treatment of osteoporosis has a good clinical effect, but the mechanism of drug intervention in bone metabolism is not yet completely clear. In this paper, the recent studies on osteoclast biology and interventions and mechanisms of Chinese medicine on osteoclasts from the perspective of OPG/RANKL/RANK signaling pathway are summarized through reviewing the relevant literatures both at home and abroad.